Evaluation of Oral Antiretroviral Drugs in Mice With Metabolic and Neurologic Complications - Tsai, Fuu-Jen; Ho, Mao-Wang; Lai, Chih-Ho; Chou, Chen-Hsing; Li, Ju-Pi; Cheng, Chi-Fung; Wu, Yang-Chang; Liu, Xiang; Tsang, Hsinyi; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; et al. (Frontiers in Pharmacology, 2018)
Antiretroviral (ART) drugs has previously been associated with lipodystrophic syndrome, metabolic consequences, and neuropsychiatric complications. ART drugs include 3 main classes of protease inhibitors (PIs), nucleoside analog reverse transcriptase inhibitors (NRTIs), and non-nucleoside reverse transcriptase inhibitors (NNRTIs). Our previous work demonstrated that a high risk of hyperlipidemia was observed in HIV-1-infected patients who received ART drugs in Taiwan. Patients receiving ART drugs containing either Abacavir/Lamivudine (Aba/Lam; NRTI/NRTI), Lamivudine/Zidovudine (Lam/Zido; NRTI/NRTI), or Lopinavir/Ritonavir (Lop/Rit; PI) have the highest risk of hyperlipidemia. The aim of this study was to investigate the effects of Aba/Lam (NRTI/NRTI), Lam/Zido (NRTI/NRTI), and Lop/Rit (PI) on metabolic and neurologic functions in mice. Groups of C57BL/6 mice were administered Aba/Lam, Lam/Zido, or Lop/Rit, orally, once daily for a period of 4 weeks. The mice were then extensively tested for metabolic and neurologic parameters. In addition, the effect of Aba/Lam, Lam/Zido, and Lop/Rit on lipid metabolism was assessed in HepG2 hepatocytes and during the 3T3-L1 preadipocyte differentiation. Administration with Aba/Lam caused cognitive and motor impairments in mice, as well as their metabolic imbalances, including alterations in leptin serum levels. Administration with Lop/Rit also caused cognitive and motor impairments in mice, as well as their metabolic imbalances, including alterations in serum levels of total cholesterol, and HDL-c. Treatment of mice with Aba/Lam and Lop/Rit enhanced the lipid accumulation in the liver, and the decrease in AMP-activated protein kinase (AMPK) phosphorylation and/or its downstream target acetyl-CoA carboxylase (ACC) protein expression. In HepG2 hepatocytes, Aba/Lam, Lam/Zido, and Lop/Rit also enhanced the lipid accumulation and decreased phosphorylated AMPK and ACC proteins. In 3T3-L1 pre-adipocyte differentiation, Aba/Lam and Lop/Rit reduced adipogenesis by decreasing expression of transcription factor CEBPb, implicating the lipodystrophic syndrome. Our results demonstrate that daily oral administration of Aba/Lam and Lop/Rit may produce cognitive, motor, and metabolic impairments in mice, regardless of HIV-1 infection.